2017
DOI: 10.1038/srep45283
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise analysis of MIR9 loci identifies miR-9-5p to be involved in Oestrogen regulated pathways in breast cancer patients

Abstract: miR-9 was initially identified as an epigenetically regulated miRNA in tumours, but inconsistent findings have been reported so far. We analysed the expression of miR-9-5p, miR-9-3p, pri-miRs and MIR9 promoters methylation status in 131 breast cancer cases and 12 normal breast tissues (NBTs). The expression of both mature miRs was increased in tumours as compared to NBTs (P < 0.001) and negatively correlated with ER protein expression (P = 0.005 and P = 0.003, for miR-9-3p and miR-9-5p respectively). In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 58 publications
2
22
0
2
Order By: Relevance
“…A subset of identified miRNAs was differentially regulated in ER− versus ER+ tumors, regardless of race. Top DEmiRs include miR-934, miR-9-3p/5p, miR-18a/18b, miR-135b and miR-190b, which showed expression changes consistent with results from our analysis of the TCGA dataset and from several previous studies (15,16,(23)(24)(25)(26). These observations are in line with the fact that most published studies have focused exclusively on EAs.…”
Section: Discussionsupporting
confidence: 91%
“…A subset of identified miRNAs was differentially regulated in ER− versus ER+ tumors, regardless of race. Top DEmiRs include miR-934, miR-9-3p/5p, miR-18a/18b, miR-135b and miR-190b, which showed expression changes consistent with results from our analysis of the TCGA dataset and from several previous studies (15,16,(23)(24)(25)(26). These observations are in line with the fact that most published studies have focused exclusively on EAs.…”
Section: Discussionsupporting
confidence: 91%
“…Few recent studies in gynaecological cancer research have described an association of miRNA and estrogen signalling. Most of them have described the role of miRNA to regulate ER expression and estrogen-associated molecules [15,16]. How E2 may interfere with the whole miRNA expression profile in the cardiovascular system is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that serum exosomal miR-9-5p was up-regulated in early-stage GC. Likewise, up-regulation of miR-9-5p was observed in both breast cancer and lung cancer, which promoted tumor proliferation, invasion, and metastasis (Barbano et al, 2017). However, functional roles of miR-146b-5p and miR-9-5p in GC remain unknown.…”
Section: Discussionmentioning
confidence: 99%